2018
DOI: 10.1177/0954405418805604
|View full text |Cite
|
Sign up to set email alerts
|

Drilling of micro-holes on titanium alloy using pulsed Nd:YAG laser: Parametric appraisal and prediction of performance characteristics

Abstract: Laser drilling is a preferable method in drilling micro and slender holes because of its non-physical contact between the tool and the workpiece leading to elimination of the problems like chatter and vibration. In this article, an experimental investigation of the laser drilling process is carried out on thin sheet (0.5 mm) of titanium alloy (Ti6Al4V) using pulsed Nd:YAG laser. The study investigates the effect of laser parameters such as laser energy, pulse repetition rate, pulse width and gas pressure on ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…When a laser beam with high pulse energy interacts with the top side of the workpiece, it melts and vaporizes the material instantly and increases the mean (entrance) hole diameter [12]; however, the intensity of the laser beam decreases as it passes through the thickness, which results in a small exit hole diameter, less material removal, and produces a high hole taper. This variation is consistent with the findings of Chatterjee et al [37] and Yilbas [12].…”
Section: Single-pulse Drillingsupporting
confidence: 93%
“…When a laser beam with high pulse energy interacts with the top side of the workpiece, it melts and vaporizes the material instantly and increases the mean (entrance) hole diameter [12]; however, the intensity of the laser beam decreases as it passes through the thickness, which results in a small exit hole diameter, less material removal, and produces a high hole taper. This variation is consistent with the findings of Chatterjee et al [37] and Yilbas [12].…”
Section: Single-pulse Drillingsupporting
confidence: 93%
“…The intensity of the laser beam decreases due to diffraction as it penetrates, which increases the hole taper. Similar findings have been observed by Sarfraz et al 15 and Chatterjee et al 42 Influence of gas pressure and gas flow rate on hole taper. The effects of gas pressure and gas flow rate on hole taper are revealed in Figure 8.…”
Section: Investigationsupporting
confidence: 89%
“…Moreover, an increase in pressure does not permit the molten metal to set down inside the hole cavity. Thus, hole taper reduces when higher gas pressure is used which is in accordance with the findings of Chatterjee et al 42 A similar trend has been observed with the increase in gas flow rate because higher compressed air flow rate increases the localised temperature due to its combustible supportability and results in efficient removal of the material from the hole exits which results in lower hole taper, as stated by Nawaz et al 20 Influence of pulse energy and pulse duration on drilling cost. Figure 9 illustrates the response of pulse energy and pulse duration on drilling costs.…”
Section: Investigationsupporting
confidence: 84%
“…However, titanium alloys have high chemical activity, low thermal conductivity and low elastic modulus, which cause a high cutting temperature and likely reaction with the carbide tool materials in the cutting/ milling process. 1 The above characteristics of titanium alloys have significant effects on the tool life, tool consumption and wear resistance of the tool surface. 2,3 At present, many scholars have shown great interest in improving the friction characteristics between the tool and the workpiece (titanium alloys) by changing the surface morphology of the tool.…”
Section: Introductionmentioning
confidence: 99%